Long Non-Coding RNAs Differentially Expressed in Swine Fetuses - Campos F.G. (2024)
© 2024 by the authors.Long non-coding RNAs (lncRNAs) are non-coding transcripts involved in various biological processes. The Y chromosome is known for determining the male sex in mammals. LncRNAs on the Y chromosome may play important regulatory roles. However, knowledge about their action mechanisms is still limited, especially during early fetal development. Therefore, we conducted this exploratory study aiming to identify, characterize, and investigate the differential expression of lncRNAs between male and female swine fetuses at 35 days of gestation. RNA-Seq libraries from 10 fetuses were prepared and sequenced using the Illumina platform. After sequencing, a data quality control was performed using Trimmomatic, alignment with HISAT2, and transcript assembly with StringTie. The differentially expressed lncRNAs were identified using the limma package of the R software (4.3.1). A total of 871 potentially novel lncRNAs were identified and characterized. Considering differential expression, eight lncRNAs were upregulated in male fetuses. One was mapped onto SSC12 and seven were located on the Y chromosome; among them, one lncRNA is potentially novel. These lncRNAs are involved in diverse functions, including the regulation of gene expression and the modulation of chromosomal structure. These discoveries enable future studies on lncRNAs in the fetal stage in pigs.